2019
DOI: 10.1017/s0007114518003860
|View full text |Cite
|
Sign up to set email alerts
|

Associations between urinary iodine concentration, lipid profile and other cardiometabolic risk factors in adolescents: a cross-sectional, population-based analysis

Abstract: Low urinary iodine concentration (UIC) is associated with dyslipidaemia in adults but is not well characterised in adolescents. Because dyslipidaemia is a cardiovascular risk factor, identifying such an association in adolescents would allow for the prescription of appropriate measures to maintain cardiovascular health. The present study addresses this question using data in the 2001–2012 National Health and Nutrition Examination Survey for 1692 adolescents aged 12–19 years. Primary outcomes were UIC, cardiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The National Health and Nutrition Examination Survey (NHANES) 2007–2012 reported that subjects with the lowest decile of UIC were more likely to be at risk for elevated total cholesterol (TC) (adjusted odds ratio (aOR) = 1.51) and elevated low-density lipoprotein (LDL) cholesterol (aOR = 1.58), compared to those with the highest decile of UIC ( 21 ). US adolescents with low UIC had a significantly higher risk of hypercholesterolemia, elevated non-high-density lipoprotein (HDL), and elevated LDL compared to those with normal UIC ( 22 ). RCTs have reported that iodine supplementation reduces hypercholesterolemia incidence in overweight women ( 42 ) and also decreased serum LDL-C levels in overweight Japanese adults ( 34 ).…”
Section: Clinical Research On the Correlation Between Iodine Status A...mentioning
confidence: 99%
“…The National Health and Nutrition Examination Survey (NHANES) 2007–2012 reported that subjects with the lowest decile of UIC were more likely to be at risk for elevated total cholesterol (TC) (adjusted odds ratio (aOR) = 1.51) and elevated low-density lipoprotein (LDL) cholesterol (aOR = 1.58), compared to those with the highest decile of UIC ( 21 ). US adolescents with low UIC had a significantly higher risk of hypercholesterolemia, elevated non-high-density lipoprotein (HDL), and elevated LDL compared to those with normal UIC ( 22 ). RCTs have reported that iodine supplementation reduces hypercholesterolemia incidence in overweight women ( 42 ) and also decreased serum LDL-C levels in overweight Japanese adults ( 34 ).…”
Section: Clinical Research On the Correlation Between Iodine Status A...mentioning
confidence: 99%